1997
DOI: 10.1523/jneurosci.17-20-07796.1997
|View full text |Cite
|
Sign up to set email alerts
|

Pathfinding by Identified Zebrafish Motoneurons in the Absence of Muscle Pioneers

Abstract: To identify the cellular cues that guide zebrafish neuronal growth cones to their targets, we examined interactions between identified motor growth cones and identified muscle fibers and tested whether these fibers were required for growth cone navigation. Caudal primary motoneurons (CaPs) and middle primary motoneurons (MiPs) are identified motoneurons that innervate cell-specific regions of the myotome. Growth cones of both cells initially extend along a common pathway and then pause at a set of identified m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 66 publications
2
89
0
Order By: Relevance
“…At 18·h.p.f., the time of first movements, still only a medial portion of the somite contains fibres with an orientation in a preferential direction, with all fibres oriented more or less parallel to the notochord (Fig.·7C). These muscle pioneer cells perform the initial contractions (Melancon et al, 1997). More laterally located muscle fibres do not show a preferential direction at this stage (Fig.·7D).…”
Section: Morphological Observationsmentioning
confidence: 87%
“…At 18·h.p.f., the time of first movements, still only a medial portion of the somite contains fibres with an orientation in a preferential direction, with all fibres oriented more or less parallel to the notochord (Fig.·7C). These muscle pioneer cells perform the initial contractions (Melancon et al, 1997). More laterally located muscle fibres do not show a preferential direction at this stage (Fig.·7D).…”
Section: Morphological Observationsmentioning
confidence: 87%
“…rons Melancon et al, 1997). Taking advantage of the recently well characterized secondary motoneuron-specific islet-1 promoter-driven GFP transgenic fish, we show that nicotine affects secondary motoneuron development in zebrafish.…”
Section: Nicotine Delays the Differentiation Of Spinal Neuronsmentioning
confidence: 96%
“…It has been previously reported that in zebrafish embryos, the trunk muscles start to show spontaneous contractile activity at 17 hpf and these movements are generated by acetylcholine (ACh) release from motor nerve terminals (Grunwald et al, 1988;Melançon et al, 1997). When acetylcholine binds to nicotinic acetylcholine receptors (nAChRs) expressed by the muscle cells, this binding is reported to activate dihydropyridine receptors (DHPRs) located on the surface membrane or on T-tubules, which in turn triggers the release of Ca 2+ from intracellular stores via RyRs, and hence contraction occurs (Schneider and Chandler, 1973).…”
Section: Effect Of     -Bungarotoxin and Nifedipine On The Sp1 Cmentioning
confidence: 99%